THE RELATIONSHIP BETWEEN PERCEIVED AUTONOMY SUPPORT AND PERCEIVED JUSTICE - Devani Laksmi Indyastuti (Jurnal Manajemen dan Pemasaran Jasa, 2017)
Previous studies have a little attention on the impact of perceived autonomy support on the justice. This study examines the impact of perceived autonomy support from supervisor and from environment toward perceived procedural justice and interpersonal justice. Based on self interest model and basic need theory, this study hypothesized that individual’s perception of autonomy supported both from supervisor and work environment would affect his/ her perception of procedural. Based on need fulfillment theory, this study hypothesized that individuals’perception of autonomy supported both from supervisor and work environment affect interpersonal justice. This study used 234 lecturers for sample and regression analysis for analizing the data. The results support the hypotheses that the higher individual perception of autonomy supports from both supervisor and work environment is, the higher is individual perception of procedural justice and interpersonal justice. This result implicates that supervisor should build perception of autonomy support among individuals in organization by buiding trust culture, open communication culture, supportive culture to increase the individual perception of procedural and interpersonal justice.